Respuesta :

Hello

x = 3y - 6
2x - 4y = 8
We need to start by solving 3y - 6 for x
Substitute 3y -6 for x in 2x
2x - 4y = 8
2(3y - 6) - 4y = 8
2y - 12 = 8
2y = 8 + 12
2y = 20
Divide both sides by 2
2y/2 = 20/2
y = 10

Now, substitute 10 for y in x= 3y
x = 3y - 6
x = 3(10) - 6
x = 30 - 6
x= 24

Answer : x = 24 and y=10

I hope this help!
cher
Equation 1)  x = 3y - 6
Equation 2)  2x - 4y = 8

Subtract 3y from both sides of the first equation.

1)  x - 3y = -6

Then, multiply all of the first equation by 2.

1)  2(x - 3y = -6)

1)  2x - 6y = -12
2)  2x - 4y = 8

Subtract equations.

-2y = -20

Divide both sides by -2.

y = 10

Plug in 10 for y in the first equation.

x = 3y - 6

x = 3(10) - 6

x = 30 - 6

x = -24

(10,24)

~Hope I helped!~
ACCESS MORE
EDU ACCESS